Developing an LMS-Based Cross-Platform Web Application for Improving Vocational High School Students’ Competitiveness in ASEAN Economic Community - Hary Suswanto; Ahmad Mursyidun Nidhom; Andika Bagus Nur Rahma Putra; Jehad A.H. Hammad (Pascasarjana Universitas Negeri Malang (UM), 2017)
Abstract: This study aimed at developing a cross-platform (CPL) web application of Learning Management System (LMS) for English lessons in vocational high school. The development was also an attempt to overcome students’ problems such as lack of independence and low achievement in English lesson, contrast with ASEAN Economic Community (AEC) expectation. The developed LMS-based web application could be accessed using computers or mobile devices running different operating systems (BlackBerry OS, Android, IOS). The LMS portal used artificial intelligence to detect the type of device accessing the web app and automatically adapt screen parameters of the device used. This research adapted the 10-step R&D model proposed by Dick and Carey. The research participants were two educational media experts, one subject-matter expert, and students. The data was collected through observation and closed-ended questionnaire. After the data was obtained, it was analysed, and the product was revised to comply with the criteria of acceptability for an effective learning platform.Key Words: cross, platform, AECAbstrak: Penelitian ini bertujuan untuk mengembangkan aplikasi web Learning Management System (LMS) lintas platform untuk pembelajaran Bahasa Inggris di Sekolah Menengah Kejuruan. Pengembangan media juga bertujuan mengatasi masalah siswa yang berkaitan dengan rendahnya kemandirian belajar serta pencapaiannya yang rendah dalam pembelajaran Bahasa Inggris, yang berseberangan dengan harapan Masyarakan Ekonomi ASEAN (MEA). Aplikasi LMS berbasis web yang dikembangkan dapat diakses melalui perangkat komputer atau telepon genggam dengan sistem operasi yang berbeda (Blackberry OS, Android, IOS). Portal LMS menggunakan kecerdasan buatan untuk mendeteksi tipe perangkat yang mengakses aplikasi web tersebut yang dapat secara otomatis beradaptasi dengan parameter layar perangkat yang digunakan. Penelitian pengembangan ini menggunakan 10 langkah model R&D yang disarankan oleh Dick dan Carey. Dua ahli media pendidikan, ahli pembelajaran, dan siswa mengambil bagian dalam penelitian ini. Data penelitian didapatkan melalui observasi dan kuesioner pertanyaan tertutup. Setelah data didapatkan, data dianalisis dan produk direvisi berdasarkan kriteria platform pembelajaran yang efektif.Kata kunci: lintas, platform, AEC